59 Ambulance over-conveyance to the emergency department: a large data analysis of ambulance journeys. (16th April 2018) - Miles, J; O'Keeffe, C; Jacques, R; Stone, T; Mason, S
Abstract : Aim: Over-conveyance by the ambulance service is a compounding factor of emergency department (ED) crowding. Previous solutions have focused on specific patient groups which have a limited impact when compared to the whole urgent and emergency care system. This study aims to analyse non-urgent conveyances by the ambulance service that could be suitable for discharge on-scene. Results: We analysed a dataset of 1, 312, 539 patient episodes which linked all pre-hospital emergency and urgent calls to subsequent ED attendance in 2014. The study was set in a large region in England (total population 5.3 million). As well as proportion of avoidable conveyances we also examined the association with patient age, time of arrival, re-attendance and initial triage code from ambulance dispatch. Results: There were 4 04 348 (30.8%) patients transported to ED by ambulance and of these 66 220 (16.4%) were considered potentially avoidable. There were significantly increased odds of a non-urgent conveyance out of hours (OR 1.44, 95% CI: 1.41 to 1.46). Patients aged 16–34 had the largest proportion of avoidable conveyances with 24 500 (37%). There were 13 625 (21%) episodes that were received from another healthcare professional or urgent telephone number. When analysing ED diagnosis, the highest proportion were attending with minor injury and illness, and alcohol intoxication. Conclusion: One in six ambulance conveyances to ED were deemed non-urgent. The younger population had the largest amount of preventable conveyance by ambulance with diagnoses which could be treated and discharged on-scene. Pathways and interventions would provide a larger patient benefit if they were designed around patient populations as opposed to disease specific. Conflict of interest: None Funding: Funded through CLAHRC Y+H (NIHR).